Procedings of the British Machine Vision Conference 2012 2012
DOI: 10.5244/c.26.136
|View full text |Cite
|
Sign up to set email alerts
|

Fast Non-uniform Deblurring using Constrained Camera Pose Subspace

Abstract: Camera shake during exposure time often results in non-uniform blur across the entire image. Recent algorithms model the non-uniform blurry image as a linear combination of images observed by the camera at discretized poses, and focus on estimating the time fraction positioned at each pose. While these algorithms show promising results, they nevertheless entail heavy computational loads. In this work, we propose a novel single image deblurring algorithm to remove non-uniform blur. We estimate the local blur ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(86 citation statements)
references
References 23 publications
0
85
0
Order By: Relevance
“…In [30], only three rotations are used to approximate the camera motion, while in-plane translations and rotation are considered in [9,10,11]. It has been shown that these two models achieve similar performance under some assumptions [14].…”
Section: Depth-aware Deblurringmentioning
confidence: 94%
See 3 more Smart Citations
“…In [30], only three rotations are used to approximate the camera motion, while in-plane translations and rotation are considered in [9,10,11]. It has been shown that these two models achieve similar performance under some assumptions [14].…”
Section: Depth-aware Deblurringmentioning
confidence: 94%
“…Recently, the problem of removing spatially variant blur caused by camera motion has attracted much attention due to its wide range of applications [1,6,25,27,13,30,9,10,28,29,11,12]. Early work splits an image into several regions where each is modeled with a constant PSF and recovered by a uniform deblur algorithm [1,6].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Although these algorithms show promising results, they have heavy computational loads. Zhe Hu [3] had proposed a novel single image deblurring algorithm to remove non-uniform blur with lesser computational load with tolerable redundancy which constrains the camera poses into certain range of rotations.…”
Section: Literature Surveymentioning
confidence: 99%